2000
DOI: 10.1002/1097-4628(20001010)78:2<364::aid-app160>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of mercerized cotton fibers due to cellulase treatment

Abstract: Cotton fibers mercerized under the relaxed state were hydrolyzed with crude cellulase. The mercerization treatment examined included ammonia treatment, sodium hydroxide treatment, and two combined treatments using ammonia and sodium hydroxide. Crystalline regions of the mercerized fibers were hydrolyzed in the first step of hydrolysis. In this step, ammonia treatment decreased the crystallite size to a great extent due to the hydrolysis of the cellulose III crystalline phase. Cellulase treatment rendered the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…The S samples, because of their extraordinary level of intracrystalline swelling, enhanced the response of the enzyme to a higher extent 14, 19, 20. In the case of ethylenediamine also, intracrystalline swelling has been reported to occur;18 this results in a higher response of enzymes.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The S samples, because of their extraordinary level of intracrystalline swelling, enhanced the response of the enzyme to a higher extent 14, 19, 20. In the case of ethylenediamine also, intracrystalline swelling has been reported to occur;18 this results in a higher response of enzymes.…”
Section: Resultsmentioning
confidence: 96%
“…In the meantime, neutral cellulases are generally recommended because of their resistance to the backstaining of garments 13. Previous studies have indicated that mercerization is effective in increasing the accessibility of fibers to the cellulase enzyme,14, 15 but there is very limited information available4 on the effect of other intracrystalline swelling agents or an intercrystalline swelling agent on the enzymatic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3 This was because the crystallite surface was deaggregated by the cellulase complex and rendered greatly accessible to water molecules. 3 Water sorption of the fiber first decreased upon endocellulase treatment, as shown in Figure 4. This suggested the preferable hydrolysis of the disordered regions without the deaggregation of the crystallite surface, different from the hydrolysis with the cellulase.…”
Section: Structural Change Of Fiber In Response To Endocellulasesmentioning
confidence: 99%
“…Recently, we found that the crystallite surface of cotton fiber was activated and water sorption was considerably increased due to cellulase treatment. 3 The development of gene-cloning procedures has made it possible to produce a cellulase which attacks hydrolytic points in disordered regions 4 and which has endocellulase activity. The endocellulases can eliminate fabric fuzz, which probably includes a large number of disordered regions, to improve the appearance of fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…It converts the cellulose chain from cellulose I to cellulose II [3][4][5]. A signi cant improvement in dye a nity, colour strength, lustre, tensile strength and the smoothness of cotton fabric also occurred due to mercerisation [1,6,7]. e degree of change depends on di erent parameters, such as processing time, processing temperature, tension, the concentration of caustic soda, etc.…”
Section: Introductionmentioning
confidence: 99%